Identification of antigen B (AgB) Gene polymorphism in cattle and sheep isolates of Echinococcus granulosus and investigation of effects on serological diagnosis - Kesik, Harun Kaya; Simsek, Sami; Kilinc, Seyma Gunyakti; Koroglu, Ergun (Elsevier, 2019)
Cystic Echinococcosis (CE) is a worldwide common helminth disease caused by the larval form of Echinococcus granulosus. The aim of this study is to determine the genetic differences between distinct isolates of E. granulosus obtained from cattle and sheep and determine the polymorphism of the AgB1 gene by DNA sequence analysis, as well as investigating its relationship with serological response using ELISA and Western Blot tests. For this aim, germinal membranes of hydatid cysts of 30 cattle and 30 sheep from the provinces of Elazig and Erzincan in Turkey and serum samples of these animals were collected. Following isolation of the total genomic DNA, the 12S rRNA gene of all isolates was amplified by PCR for genetic characterization, and the mt - CO1 gene region was examined by DNA sequence analysis. The gDNAs were then amplified by PCR using AgB1-specific primers, and genetic variation was investigated by DNA sequence analysis. At the final stage, all serum samples were analyzed by ELISA and Western Blot tests using a partially purified hydatid cyst fluid antigen. As a result, 114 (95%) of the 120 isolates were determined to be E. granulosus sensu stricto by using 12S rRNA-PCR. Subsequently, the DNA sequence analysis of the remaining 6 samples of the mt - CO1 gene revealed that all samples were E. granulosus sensu stricto. According to the DNA sequence analysis that followed, nucleotide changes in the AgB1 gene were observed in 13 (10.8%) of 120 samples. With this study, 9 (69.2%) out of 13 hydatid cysts in which polymorphism was detected by DNA sequence analysis in their AgB1 gene were found to be positive with ELISA, and 6 (46.1%) were found positive by WB. While 80 (74.7%) of 107 non-polymorphic samples in the AgB1 gene were found to be positive with ELISA, and 75 (70.9%) were positive with WB. As a result, variation in different ratios was determined in the AgB1 gene of E. granulosus sensu stricto, and it was determined that this had a partial effect on serological response.
Keywords: Echinococcus granulosus; Antigen B; Polymorphism; Sheep; Cattle